Efeito de ambientes e densidades de semeadura em soja, visando à produção de biodiesel - Almeida, Bernardo Coutinho (Universidade Federal do Tocantins, 2017)
The objective of this study was to evaluate the effect of different environments and plant densities in three soybean cultivars. Were performed five competition assays in the agricultural year 2012/2013, three in University Campus of Gurupi - TO (Gurupi I - 05/12/2012, Gurupi II - 20/12/2012 e Gurupi III - 07/01/2013) (280 m de altitude, 11°43’ S, e 49°04’ W) and two in the University Campus of Palmas - TO (Palmas I - 28/11/2012 e Palmas II - 15/12/2012) (220m de altitude, 10o45' S e 47o14' W). The experimental design utilized was a randomized blocks, with nine treatments and three replications. The treatments were disposed in a 3x3 factorial, constituted for three cultivars (P98Y70, M8766RR e M9144RR) and three planting densities (6, 10 and 14 plants per linear meter). Were evaluated the characteristics: grain yield (kg ha-1), Oil content (%) and oil yield (kg ha-1). Statistical analyzes were performed with the aid of SISVAR program. Based on the results it is observed that plantations outside the traditional growing season adversely affects all studied characteristics. The highest densities are the most favorable for oil yield, but with no effect on grain yield and oil content. The M9144RR and M8766RR cultivars exhibit favorable characteristics for the production of Biodiesel.